2020
DOI: 10.1371/journal.ppat.1007969
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae type VI secretion system-mediated microbial competition is PhoPQ controlled and reactive oxygen species dependent

Abstract: Klebsiella pneumoniae is recognized as an urgent threat to human health due to the increasing isolation of multidrug resistant strains. Hypervirulent strains are a major concern due to their ability to cause life-threating infections in healthy hosts. The type VI secretion system (T6SS) is widely implicated in microbial antagonism, and it mediates interactions with host eukaryotic cells in some cases. In silico search for genes orthologous to T6SS component genes and T6SS effector genes across 700 K. pneumonia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(134 citation statements)
references
References 105 publications
1
133
0
Order By: Relevance
“…Although >25% Gram-negative bacteria encode T6SSs, wild-type NTUH-2044 has been confirmed to outcompete Salmonella Typhimurium, E. coli, and T6SS-null K. pneumoniae in a T6SS-dependent manner, and the frequency of T6SSs in KLA strains is significantly higher compared to that in the intestinal-colonizing strains, suggesting that T6SSs may confer an advantage for hvKP survival (Clemens et al, 2018;Hsieh et al, 2019). Another study reported that in bacterial competition, K. pneumoniae T6SSs were activated by the PhoPQ system, followed by the use of effectors to kill E. coli prey that lack T6SS immunity genes (Storey et al, 2020). Moreover, the overexpression of a T6SS effector in the carbapenemaseproducing K. pneumoniae strain, the phospholipase Tle1, was found to inhibit the growth of E. coli (Liu et al, 2017).…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…Although >25% Gram-negative bacteria encode T6SSs, wild-type NTUH-2044 has been confirmed to outcompete Salmonella Typhimurium, E. coli, and T6SS-null K. pneumoniae in a T6SS-dependent manner, and the frequency of T6SSs in KLA strains is significantly higher compared to that in the intestinal-colonizing strains, suggesting that T6SSs may confer an advantage for hvKP survival (Clemens et al, 2018;Hsieh et al, 2019). Another study reported that in bacterial competition, K. pneumoniae T6SSs were activated by the PhoPQ system, followed by the use of effectors to kill E. coli prey that lack T6SS immunity genes (Storey et al, 2020). Moreover, the overexpression of a T6SS effector in the carbapenemaseproducing K. pneumoniae strain, the phospholipase Tle1, was found to inhibit the growth of E. coli (Liu et al, 2017).…”
Section: Other Virulence Factorsmentioning
confidence: 99%
“…DUF2345 domains can perform additional functions. In Acinetobacter baumannii , the DUF2345 of VgrG is essential for T6SS assembly, while the VgrG4 DUF2345 domain of Klebsiella pneumoniae is itself an antibacterial and antifungal toxic effector inducing response to reactive oxygen species (Lopez et al, 2020; Storey et al, 2020). Rhs are large proteins that were first identified as recombination‐prone loci in chromosomes (Lin et al, 1984).…”
Section: Effector Loading and Deliverymentioning
confidence: 99%
“…The strain K. pneumoniae kp52145 [ 31 ], also known as CIP52.145 [ 32 ], belongs to the K. pneumoniae KpI group that includes the majority of strains associated with human infection, including several multidrug-resistant and hypervirulent clones [ 33 ]. It is then a good model for searching for novel potential mechanisms of antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%